A study on Al(III) and Fe(II) ions sorption by cattle manure vermicompost - Jordão, Cláudio Pereira; Fernandes, Raphael Bragança A.; Ribeiro, Kamilla de Lima; Barros, Priscila M. de; Fontes, Mauricio Paulo F.; Souza, Francianny Maria de Paula (Water, Air, & Soil Pollution, 2010)
Cattle manure vermicompost has been used for the adsorption of Al(III) and Fe(II) from both synthetic solution and kaolin industry wastewater. The optimum conditions for Al(III) and Fe(II) adsorption at pH 2 (natural pH of the wastewater) were particle size of ≤250 µm, 1 g/10 mL adsorbent dose, contact time of 4 h, and temperature of 25°C. Langmuir and Freundlich adsorption isotherms fitted reasonably well in the experimental data, and their constants were evaluated, with R 2 values from 0.90 to 0.98. In synthetic solution, the maximum adsorption capacity of the vermicompost for Al(III) was 8.35 mg g−1 and for Fe(II) was 16.98 mg g−1 at 25°C when the vermicompost dose was 1 g 10 mL−1, and the initial adjusted pH was 2. The batch adsorption studies of Al(III) and Fe(II) on vermicompost using kaolin wastewater have shown that the maximum adsorption capacities were 1.10 and 4.30 mg g−1, respectively, at pH 2. The thermodynamic parameter, the Gibbs free energy, was calculated for each system, and the negative values obtained confirm that the adsorption processes were spontaneous.
Keywords: Vermicompost; Aluminum; Iron; Adsorption; Langmuir and Freundich isotherms; Kaolin wastewater